Răspuns :
Voi folosii formula ,, a^m × b^m =(a×b)^m (semnul ^ inseamna la puterea ...)
j) [(-5)×(-6)]^3 = 30^3 ;
k) [7×(-9)]^4 = (-63)^4 = 63^4 ;
l) [(-7)×(-6)]^2 = 42^2 ;
m) [12×(-3)]^5=(-36)^5= - 36^5 ;
n) [(-5)×2]^3=(-10)^3= - 10^3 ;
o) [(-15:3]^3= (-5)^3= - 5^3 ;
p) [(-42):7]^5=(-6)^5= - 6^5 ;
j) [(-5)×(-6)]^3 = 30^3 ;
k) [7×(-9)]^4 = (-63)^4 = 63^4 ;
l) [(-7)×(-6)]^2 = 42^2 ;
m) [12×(-3)]^5=(-36)^5= - 36^5 ;
n) [(-5)×2]^3=(-10)^3= - 10^3 ;
o) [(-15:3]^3= (-5)^3= - 5^3 ;
p) [(-42):7]^5=(-6)^5= - 6^5 ;